2011
DOI: 10.1007/s00213-011-2603-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the effects of Eugenol on neuronal ionic currents and hyperexcitability

Abstract: The synergistic blocking effects of I (Na) and I(Na(NI)) contributes to the main mechanism through which EUG affects the firing of neuronal APs and modulate neuronal hyperexcitability such as pilocarpine-induced temporal lobe seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 60 publications
5
28
0
Order By: Relevance
“…1A; p < 0.001 vs. KA alone). These results are in agreement with previously published reports (Huang et al, 2012;Müller et al, 2006;Pourgholami et al, 1999), which suggest that EUG may exert anticonvulsant activity in a KA-induced model of TLE.…”
Section: Inhibitory Effects Of Eug On Ka-induced Gcd In the Dgsupporting
confidence: 95%
See 1 more Smart Citation
“…1A; p < 0.001 vs. KA alone). These results are in agreement with previously published reports (Huang et al, 2012;Müller et al, 2006;Pourgholami et al, 1999), which suggest that EUG may exert anticonvulsant activity in a KA-induced model of TLE.…”
Section: Inhibitory Effects Of Eug On Ka-induced Gcd In the Dgsupporting
confidence: 95%
“…To confirm the beneficial effects of EUG against KA-induced seizures (Huang et al, 2012;Pourgholami et al, 1999), we evaluated whether EUG treatment delayed KA-induced seizure onset. Our results showed that 100 mg/kg EUG plus KA had no significant effect on seizure susceptibility (p = 0.074 vs. KA alone).…”
Section: Inhibitory Effects Of Eug On Ka-induced Gcd In the Dgmentioning
confidence: 99%
“…and methylscopolamine (25 mg/kg; s.c.), before seizures were induced with pilocarpine injections (60 mg/kg; s.c.). All rats demonstrated behavioral characteristics during epileptic seizures that were similar to those reported previously [6], [27], [28]. Mouth and facial movements, head bobbing and nodding, scratching, masticatory automatisms, and exploratory behavior were observed within 15 to 20 min (stages 1–2).…”
Section: Methodssupporting
confidence: 80%
“…The present study showed a negative chronotropic effect in Daphnia magna induced by CO alone at both concentrations, however more increased bradycardia was noted at the higher concentration of CO. The effects are similar to those observed by other authors who found that CO and other anaesthetics induce hypotension and bradycardia in fish and mammals (Lahlou et al, 2004;Mitchell et al, 2009;Huang et al, 2012). It is known that inhibition of heart rate caused by CO is associated with biological properties of eugenol which affects cardiac muscles acting as a Na + and Ca 2+ channel blocker, however its mechanisms of action on ionic channels both in vertebrates and invertebrates are not completely understood (Bekker and Krijgsman, 1951;Dyson et al, 1998;Chung et al, 2008).…”
Section: Heart Activitysupporting
confidence: 75%